(untitled) (International journal of artificial intelligence, 2025)
The collaboration between preschool educational institutions and families plays a crucial role in the social and moral education of children. This article explores the significance of this partnership, analyzing various factors that influence children's development. The study emphasizes the necessity of coordinated efforts in nurturing socially responsible and morally conscious individuals. The article also presents innovative approaches and effective methodologies for enhancing cooperation between educators and parents.